2022
DOI: 10.3389/fphar.2022.881835
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cordyceps sinensis and its Extracts in the Treatment of Diabetic Kidney Disease: A Review

Abstract: Diabetic kidney disease (DKD) is the major reason of chronic kidney disease (CKD)-caused end-stage renal failure (ESRF), and leads to high mortality worldwide. At present, the treatment of DKD is mainly focused on controlling the hyperglycemia, proteinuria, and hypertension, but is insufficient on the effective delay of DKD progression. Cordyceps sinensis is a kind of wild-used precious Chinese herb. Its extracts have effects of nephroprotection, hepatoprotection, neuroprotection, and protection against ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…Its extracts have effects of nephroprotection, hepatoprotection, neuroprotection, and protection against ischemia/reperfusion-induced injury, as well as antiinflammatory and anti-oxidant activities. 42 Research on the isolation and culture of C. sinensis began in the late 43 Till now, 35 Cordyceps species have been reported in the literature to have medicinal properties or to isolate bioactive compounds. 44 Of these 35 species, five have been developed for clinical application as drugs with national standards: Xinganbao capsules developed from Gliocladium roseum, Ningxinbao capsules from Cephalosporium sinensis, Zhiling capsules from Mortierella hepiali in 1985, Jinshuibao capsules developed from Paecilomyces hepialid in 1987, and Bailing capsules from Hirsutella sinensis in 1988.…”
Section: Medicines Developed From Fermented Mycelium Of C Sinensismentioning
confidence: 99%
“…Its extracts have effects of nephroprotection, hepatoprotection, neuroprotection, and protection against ischemia/reperfusion-induced injury, as well as antiinflammatory and anti-oxidant activities. 42 Research on the isolation and culture of C. sinensis began in the late 43 Till now, 35 Cordyceps species have been reported in the literature to have medicinal properties or to isolate bioactive compounds. 44 Of these 35 species, five have been developed for clinical application as drugs with national standards: Xinganbao capsules developed from Gliocladium roseum, Ningxinbao capsules from Cephalosporium sinensis, Zhiling capsules from Mortierella hepiali in 1985, Jinshuibao capsules developed from Paecilomyces hepialid in 1987, and Bailing capsules from Hirsutella sinensis in 1988.…”
Section: Medicines Developed From Fermented Mycelium Of C Sinensismentioning
confidence: 99%
“…Additionally, Jin Shui Bao capsules can protect renal tubular epithelial cells, inhibit renal microvascular lesions, promote homeostasis, and preserve the renal microvessels. [20]…”
Section: Jin Shui Bao and Diabetic Nephropathymentioning
confidence: 99%
“…Additionally, Jin Shui Bao capsules can protect renal tubular epithelial cells, inhibit renal microvascular lesions, promote homeostasis, and preserve the renal microvessels. [20] Currently, the primary medicines used to treat DN are angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs). Studies have shown that some Chinese patent medicines and microcirculation-improving treatments can reduce urinary protein levels in patients with DN.…”
Section: Jin Shui Bao and Chronic Kidney Diseasementioning
confidence: 99%
“…Cordyceps sinensis is a rare wild Chinese herbal medicine, with the function of nourishing the lung and kidney according to the theory of traditional Chinese medicine. [7] Jinshuibao (JSB) is an extract of Cordyceps sinensis, [8] which contains nucleosides, amino acids, sterols, polysaccharides and other components. [9] Modern pharmacology shows that, [7,10,11] it has antibacterial, anti-inflammatory, anti-hyperglycemic, lowering serum cholesterol, triglyceride and lipid peroxide, increasing blood supply to heart and brain, inhibiting platelet aggregation, anti-fibrosis, nourishing lung and kidney, anti-tumor and other effects.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Jinshuibao (JSB) is an extract of Cordyceps sinensis, [8] which contains nucleosides, amino acids, sterols, polysaccharides and other components. [9] Modern pharmacology shows that, [7,10,11] it has antibacterial, anti-inflammatory, anti-hyperglycemic, lowering serum cholesterol, triglyceride and lipid peroxide, increasing blood supply to heart and brain, inhibiting platelet aggregation, anti-fibrosis, nourishing lung and kidney, anti-tumor and other effects. JSB has been applied in clinical for a long time, and has been proved to be effective in the treatment of many diseases, such as diabetes nephropathy, chronic nephritis, bronchial asthma, chronic bronchitis, viral hepatitis, lung cancer, etc.…”
Section: Introductionmentioning
confidence: 99%